Isolation of Extracellular Polymeric Substances from Biofilms of the Thermoacidophilic Archaeon Sulfolobus acidocaldarius - Jachlewski, Silke; Jachlewski, Witold D.; Linne, Uwe; Bräsen, Christopher; Wingender, Jost; Siebers, Bettina (Frontiers in Bioengineering and Biotechnology, 2015)
Extracellular polymeric substances (EPS) are the major structural and functional components of microbial biofilms. The aim of this study was to establish a method for EPS isolation from biofilms of the thermoacidophilic archaeon Sulfolobus acidocaldarius as a basis for EPS analysis. Biofilms of S. acidocaldarius were cultivated on the surface of gellan gum-solidified Brock medium at 78 °C for 4 days. Five EPS extraction methods were compared, including shaking of biofilm suspensions in phosphate buffer, cation-exchange resin (CER) extraction and stirring with addition of EDTA, crown ether or NaOH. With respect to EPS yield, impact on cell viability and compatibility with subsequent biochemical analysis, the CER extraction method was found to be the best suited isolation procedure resulting in the detection of carbohydrates and proteins as the major constituents and DNA as a minor component of the EPS. Culturability of CER-treated cells was not impaired. Analysis of the extracellular proteome using two-dimensional gel electrophoresis resulted in the detection of several hundredshundred of protein spots, mainly with molecular masses of 25 kDa to 116 kDa and pI values of 5 to 8. Identification of proteins suggested a cytoplasmic origin for many of these proteins, possibly released via membrane vesicles or biofilm-inherent cell lysis during biofilm maturation. Functional analysis of EPS proteins, using fluorogenic substrates as well as zymography, demonstrated the activity of diverse groups of enzymes such as proteases, lipases, esterases, phosphatases and glucosidases. In conclusion, the CER extraction method, as previously applied to bacterial biofilms, also represents a suitable method for isolation of water soluble EPS from the archaeal biofilms of S. acidocaldarius, allowing the investigation of composition and function of EPS components in these types of biofilms.